2014
DOI: 10.1590/s1806-66902014000400013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da morfologia interna de sementes de Terminalia argentea (Combretaceae) pelo teste de raios X

Abstract: RESUMO -As espécies florestais, particularmente as de Cerrado, são caracterizadas pela alta ocorrência de predação, frutos vazios e deficiência na formação do embrião. O objetivo do presente trabalho foi avaliar a morfologia interna de sementes de Terminalia argentea Mart. et Zucc. pelo teste de raios X e verificar a sua relação com a germinação. O experimento foi conduzido no Laboratório de Análise de Imagens do Departamento de Produção Vegetal da Escola Superior "Luis de Queiroz" na cidade de Piracicaba, SP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
1
23
0
4
Order By: Relevance
“…It also allowed seed morphology to be related to germination or morphology of seedlings of diverse agricultural and forest species (Burg et al, 1994;Battisti et al, 2000;Machado and Cicero, 2003;Oliveira et al, 2003;Mondo and Cicero, 2005;Pupim et al, 2008;Pinto et al, 2009a;Carvalho et al, 2010;Gagliardi and Marcos-Filho, 2011;Kobori et al, 2012;Silva, P.P. et al, 2014;Gomes et al, 2014;Silva, V.N. et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also allowed seed morphology to be related to germination or morphology of seedlings of diverse agricultural and forest species (Burg et al, 1994;Battisti et al, 2000;Machado and Cicero, 2003;Oliveira et al, 2003;Mondo and Cicero, 2005;Pupim et al, 2008;Pinto et al, 2009a;Carvalho et al, 2010;Gagliardi and Marcos-Filho, 2011;Kobori et al, 2012;Silva, P.P. et al, 2014;Gomes et al, 2014;Silva, V.N. et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray test has also been effective in identifying injuries from "moisture" in soybean seeds (Obando-Flor et al, 2004;Forti et al, 2010) and from stink bugs in soybean (Obando-Flor et al, 2004;Pinto et al, 2009b) and in common bean (Forti et al, 2008) seeds, evaluation of fissures in rice seeds (Menezes et al, 2012), and mechanical injuries in maize seeds (Carvalho et al, 1999;Cicero and Banzatto-Junior, 2003;Gomes-Junior and Cicero, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that X-ray imaging allows the improvement of the physical and physiological quality of seed lots by removing internally damaged, poorly formed, or empty seeds, as was observed for Cecropia pachystachya Trec. seeds (Pupim et al, 2008), seeds of arboreal Lauraceae species (Carvalho et al, 2009), Tabebuia heptaphylla (Amaral et al, 2011), and Terminalia argentea (Gomes et al, 2014). It also allows for the identification of damaged or abnormal embryos and their removal from work samples, as observed in Lithraea molleoides (Machado & Cicero, 2003) and Malpighia emarginata D.C. (Nassif & Cicero, 2006).…”
Section: Eamentioning
confidence: 99%
“…The native forest species undergo high rates of predation, insect attack, empty fruit, and deficiency in the formation of the embryo, all of which compromise the performance of the seed and the establishment of seedlings in the field (Gomes, Martins, Martins, & Junior, 2014). Studies on the quality of the native forest seeds represent only 0.1% of the species found in the Rules for Seed Testing (Brasil, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation